2015
DOI: 10.15244/pjoes/29202
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Multiple Antibiotic and Heavy Metal Resistance of the Bacteria Isolated from the Küçükçekmece Lagoon, Turkey

Abstract: Küçükçekmece Lagoon is utilized as a recreational area for the locals. However, as a result of increasing population and industrialization, it was contaminated with faecal effluents and heavy metals. Thus, it poses a significant risk for public health [1]. Human and animal pathogenic and potentially pathogenic bacteria are continually introduced with wastewater into the water bodies [2]. Waters contaminated with faecal human and cattle waste are generally considered a greater risk for human health [3, 4]. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The recorded MAR index value was 0.187. Similar to this study result, the low MAR index for E. coli isolates in Kucukcekmece Lagoon (Istanbul, Turkey) was determined as 0.14 (Kimiran-Erdem et al, 2015). A recent study carried out in Karasu River; MAR index values of isolated E. coli strains were in range from 0.4-0.7 (Avsar, 2018) which these values higher than the result of this study.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The recorded MAR index value was 0.187. Similar to this study result, the low MAR index for E. coli isolates in Kucukcekmece Lagoon (Istanbul, Turkey) was determined as 0.14 (Kimiran-Erdem et al, 2015). A recent study carried out in Karasu River; MAR index values of isolated E. coli strains were in range from 0.4-0.7 (Avsar, 2018) which these values higher than the result of this study.…”
Section: Resultssupporting
confidence: 83%
“…In brief, MAR patterns of coliform and/or fecal coliform strains may be informed of the types (human or animal origin) of pollution in waters. Kimiran Erdem et al (2015) reported that the low MAR index was observed in E. coli of animal origin. According to this literature, it is clear that E .coli contamination in Seve Dam and Konak Pond originated waste of animals on which antibiotics were seldom or never used.…”
Section: Resultsmentioning
confidence: 99%
“…where a stands for the number of metals the isolate was resistant to, and b represents the total number of metals the isolate was tested against. A similar equation was applied by Matyar [41] and Kimiran-Erdem [42].…”
Section: Assessment Of Metal Toxicitymentioning
confidence: 99%
“…Microorganisms have been isolated from the air, water, soil, humans and animals. These organisms have even been isolated from extreme environments such as hot springs (Jardine et al, 2017), high salt environments (Shi et al, 2012), permafrost (Zhang et al, 2013), and environments with extremely elevated metal concentrations (Kimiran Erdem et al, 2015). In these natural environments, these organisms live in a balanced state, providing various ecological functions that maintain a balanced ecosystem (Dobrovol'skaya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%